"I'm in the center of the vortex": The affective chain of social media trolling. Issue 1 (18th October 2019) - Tian, Huixin; Chen, Pei‐Ying
ABSTRACT: Dominant models for the conceptualization of trolling fail to address the subjective experiences of its victims. By bringing affect into perspective, this paper explores the negative impact of trolling on individuals, drawing on data from semi‐structured interviews with 19 respondents who were trolled on popular Chinese social networks (e.g., Weibo, Zhihu, Renren ), blogs, and forums (e.g., Baidu Tieba, Tianya ). Our preliminary findings suggest that: (1) the affective chain of trolling is materialized by the social network platforms' affordability and human actors' desire for intensity, and (2) the victims of trolling were overwhelmed by the accumulated affective intensities in circulation to which they were exposed.